Study of Microstructure and Mechanical Property Degradation of SA210 A1 Boiler Tube - Peeratatsuwan, Chaiyawat; Chowwanonthapunya, Thee (International Journal of Integrated Engineering, 2020)
The comprehension of the microstructure change and mechanical property degradation are of particular importance for assessing the integrity of aging boiler tubes.This paper describes the investigation of microstructure evolution and mechanical property degradation of SA210 A1 steel used in an actual boiler condition. The investigation deals with visual inspection, chemical composition analysis, micrograph study using Energy Dispersive Spectroscopy-Scanning Electron Microscopy (EDS-SEM), tensile test and hardness test. The result showed that the prolonged operating period in the high temperature condition resulted in the reduction of the mechanical properties of the SA 210 A1 steel tube. The study also indicated the presence of the onset of the pearlite disintegration and coagulation, resulted from the microstructure degradation of the aged steel tube after the elevated temperature service in a boiler.